Tombamento ambiental: análise das decisões judiciais sobre a tutela do patrimônio cultural no âmbito dos Tribunais de Justiça - Fidelis, Rafaela Monique Vaz Cordeiro (2021)
The cultural environment consists of cultural goods, the meaning of which includes those that have historical, artistic, landscape, archaeological value, among others, reflecting the characteristics of a given society. Thus, the cultural environment arises from an intense interaction between man and nature, since that builds its environment, and all activity and perception are formed by its culture. When analyzing the cultural environment, as a complex macrosystem, the study reflects the conflict between the right to property and the right to preserved cultural heritage, both fundamental rights guaranteed in the Federal Constitution of 1988, which, far from being just a legal issue, it exposes aspects related to the origin of the Brazilian State, its cultural and political formation. In this context, the evolution and expansion of the concept of culture is examined, since the newest constitutional order establishes a specific legal regime for the protection of cultural assets in the country, insofar as it attributes to the State, with the collaboration of community, the protection and promotion of cultural heritage. However, the absence of a pluralist policy is reflected in the commitment of Brazilian doctrine and jurisprudence to define the limits of judicial action on goods of cultural interest. The objective is to approach the institute of heritage, as a modality of State intervention in any type of property, due to the preservation of the historical or artisticcultural heritage, as well as the adequacy of its content and the possibility of admitting sacrifices to the right of property. A central concern of the study is the exercise of jurisdictional control over the listed property, whose problematization consists in analyzing whether the Courts of Justice are authorized to review the action or omission of the Administration and replace it with a specific decision aimed at the protection of cultural heritage. In order to achieve this goal, the research was carried out by consulting bibliographic, jurisprudential, legislative and documentary collections, clarifying, however, that the search for documents was limited to legal proceedings involving the thematic of heritage. As a result of the scientific survey, it is ensured that it has contributed to building an understanding of the role of the Judiciary in the selection, promotion and protection of Brazilian cultural heritage, presenting the (in) coherence of decisions regarding the control of overturning acts.